Cross-Sectional study on weekday and weekend patterns of objectively measured sitting/lying, standing and stepping in obese children - Marhasiyah, Rahim; Nadzirah, A; Razif, S; Hasmiza, H; Wafa, S.W (2015)
Obese children have been highlighted as a particularly sedentary population and the possible negative effects of a sedentary lifestyle are being uncovered. Total time spent sedentary and the sedentary patterns of obese children have not been described using objective and direct measure of body inclination. Therefore, the aims of this study are to examine the patterns of objectively measured sitting/lying, standing and stepping in obese children using the ActivPALTM and to highlight possible differences in sedentary levels and patterns during weekday and weekends. One hundred and one obese children, age 9-11 years, were recruited from urban and rural schools in Kuala Terengganu. Participants wore an ActivPALTM monitor for 7 days to measure total time of daily sitting/lying, standing and stepping. The ActivPALTM output was examined using a customized macro Excel 2013. The results shows that obese children tend to spend most of their days in sitting/lying (77.8%) rather than standing (14.3%) and stepping (7.9%). There is significance different found in sitting/lying during weekends compared to weekdays (19.3 hours vs 18.4 hours; p value <0.001). Significantly more sedentary bouts were accumulated during weekdays compared to weekends (p value <0.05). Sedentary behaviour was one of the factors that contribute to childhood obesity. This is the first study in Malaysia that use activPALTM monitor to measure sedentary behaviours in obese children. Interventions that target the sedentary behaviour of obese children by displacing sitting with activity may offer most promise for reducing population levels of sedentary behaviour and physical activity levels in school children.